HADIS QODHIL HAJAT (Studi Pemikiran Ali Mustafa Yaqub) - annufairi, labib; Syaiful, Muhammad (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2026)
The Hadiths of Prophet Muhammad (peace be upon him) must be understood according to their context. Therefore, various approaches are required to interpret them, one of which involves the use of Geography. Geography can assist in accurately understanding the Hadiths, particularly those related to specific locations. Hence, geographical knowledge becomes one of the most important elements in implementing prophetic values, especially in Indonesia, which has geographical distinctions from Mecca and Medina. This study aims to explore the method used by Ali Mustafa Ya‘qub in interpreting the Hadith Qodhi Hajat. The research employs a qualitative approach, which presents data descriptively and emphasizes analysis in the process of drawing conclusions as well as in examining the dynamics of the relationships among observed phenomena through scientific reasoning. The findings of the study indicate that the quality of the Hadith Qodhi Hajat in terms of its chain of transmission (sanad) is classified as a Marfu’ Hadith. In interpreting this Hadith, Ali Mustafa Ya‘qub applies a geographical approach. The geographical approach serves as a method to determine direction or position when relieving oneself, by identifying west, east, north, and south, and then orienting oneself accordingly, in line with the content of the Qodhi Hajat Hadith.